MGA Kwento NG Guro At Kwentong Mag-Aaral: Student Assessment Processes, Challenges And Solutions In The New Normal Setup Leading To Quality Assurance Inputs - Aljon Delmo Galang; Rosie Lopez Conde; I Ketut Sudarsana (UHN IGB Sugriwa Denpasar, 2021)
This qualitative research study used narrative approach to retell the narratives of twelve (12) high school teachers on the processes, challenges, and solutions of student assessment. The investigation identifies that teachers assess the students by utilizing modules and other activities as alternatives of face-to-face instruction and assessment, using rubrics and providing feedbacks, utilizing online platforms, and involving parents. The participants also encountered challenges such as academic dishonesty, students’ attitude towards learning tasks, and lack of ICT resources. These are solved by communicating with parents, feedbacking, and alternatives means of distributing learning tasks. The findings provide insights specifically for teachers who struggle in assessing student learning in the New Normal Setup and who aim to use distance learning even in the post-pandemic class setting; and contribute inputs to quality assurance in education, considering the pandemic-impacted educational landscape